Self Concept Of Homosexuals In Pekanbaru City - Meysi Yulismida, Meysi Yulismida; Abdul Munir (Sisi Lain Realita, 2024)
Homosexuals are identified as people who have a psychological and emotional attraction to members of the same sex. Apart from that, Homosexuals also have biological needs like humans in general. Presenting oneself as heterosexual does not make it difficult for Homosexuals to establish relationships with the opposite sex. This research aims to determine the self-concept of homosexuals in the city of Pekanbaru. From the results of the research carried out, conclusions can be drawn that the process of forming self-concepts for homosexuals is different. However, all informants went through resistance, identity acceptance, namely acceptance of their sexual identity as homosexual. Effects of influence on self-concept consist of parenting patterns, depression, failure, and the environment.